Sustainable Land Use and Rural Development in Southeast Asia: Innovations and Policies for Mountainous Areas - Fröhlich, Holger L.; Schreinemachers, Pepijn; Stahr, Karl; Clemens, Gerhard (Springer Nature, 2021)
Sustainable Development; Landscape/Regional and Urban Planning; Agriculture